2020
DOI: 10.1038/s41523-020-00196-3
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of weaning-induced breast involution in women: implications for young women’s breast cancer

Abstract: In rodents, weaning-induced mammary gland involution supports increased mammary tumor incidence, growth, and progression to metastasis. Further, the protumor attributes of gland involution are COX-2 dependent and mitigated by short-duration non-steroidal anti-inflammatory drugs (NSAIDs), suggesting a potential prevention strategy. However, the transition from lactation to postweaning breast involution has not been rigorously evaluated in healthy women. Here we queried breast biopsies from healthy women (n = 11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 60 publications
2
35
0
Order By: Relevance
“…We analyzed this publicly available data set to focus on gene sets from healthy nulliparous and postpartum subjects within 2 years of their last childbirth. As anticipated from previous reports 56,57 , we observed some normal involution signatures in the postpartum normal tissue expression data sets, such as a parity signature (Supplementary Fig. 1a) and the immune infiltrate signature (Supplementary Fig.…”
Section: Resultssupporting
confidence: 87%
“…We analyzed this publicly available data set to focus on gene sets from healthy nulliparous and postpartum subjects within 2 years of their last childbirth. As anticipated from previous reports 56,57 , we observed some normal involution signatures in the postpartum normal tissue expression data sets, such as a parity signature (Supplementary Fig. 1a) and the immune infiltrate signature (Supplementary Fig.…”
Section: Resultssupporting
confidence: 87%
“…Stained sections were scanned using the Aperio AT2 slide scanner (Leica Biosystems, Wetzlar, Germany). Signal quantification was performed by Aperio ImageScope v12.1.0.5029 as described previously [ 79 ]. For quantitation, all mice and tumors found in the stained tissue section were included for every analysis, unless staining was unsuccessful as defined as loss of tissue from slide and/or failure for positive controls to stain.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies show that COX2 is dynamically regulated in mammary gland tissue across a menstrual cycle, and induced by ovarian hormones in rodents 31 , 50 . In support of menopausal status impacting COX2 expression in human breast tissue, a study of breast biopsies from healthy women showed that COX2 expression is dynamically regulated across a reproductive cycle 53 . Further, previously published studies revealed that COX2 expression in healthy, premenopausal women was highly variable, with positive CX229 or CX294 staining ranging from undetectable to high 31 , 42 , 54 .…”
Section: Discussionmentioning
confidence: 99%